PEMANFAATAN REMOTE SENSING DALAM UPAYA PEMANTAUAN PERUBAHAN LAHAN DI PUSAT KOTA SEMARANG - Septa Yudha Ardiansyah; Diah Aryati Puji Lestari (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2019)
Changes in the flow of globalization that is happening in the world are unavoidable. Various kinds of effects caused one of which is urbanization. urbanization that occurs not only in units of time but a long period of time. One indicator of the occurrence of urbanization is by marking the activity of land changes on earth. In identifying land-use changes that occur in an area, an in-depth study approach is needed, one of which is an approach using Remote Sensing. The purpose of this study is to provide a picture of a condition of land-use change activities that occur due to urbanization in the city center from time to time for 5 years. One method used is Spatial Quantitative with the Unsupervised Classification analysis method. Based on the analysis of land use through the Unsupervised Classification approach, it was found that the District of North Semarang in the past 5 years had the highest changes in land use in the Semarang City Center BWK I, II, III, amounting to 21%. The second biggest land change is West Semarang District 18% and Gajahmungkur District 13%. After identification and verification, land changes that occur are from non-developed land to be built. Types of existing built land include warehousing facilities, aviation transportation facilities, educational facilities, and settlements.